Similar biotherapeutic products in Latin America. Regulation and opportunities for patients with autoimmune diseases (2013)
Biotherapeutic products have revolutionized medicine, changing the way we can treat some chronic diseases, such as autoimmune diseases. The patent expiry and the high costs of reference biotherapeutic products, among other factors, have promoted interest in similar biotherapeutic products (SBPs), also known as biosimilars. The objective of developing an SBP is to manufacture a “highly similar” molecule to a reference biotherapeutic product, by conducting a comparability exercise that can demonstrate similar quality, safety, and efficacy. Regulations like those of the World Health Organization, the European Medicines Agency, and the Food and Drug Administration are international reference standards. Herein, we aim to point out the current status in Latin America on SBPs, focusing on regulatory issues within the context of autoimmune diseases. The regulations of Argentina, Peru, Chile, Guatemala, Panama and Costa Rica follow the World Health Organization guidelines. Other countries, such as Cuba, Mexico, Venezuela, and Brazil have regulations that take into account international standards combined with local features. In Colombia, a draft decree is under revision and the debate is ongoing. Some countries have already approved SBPs. Mexico, Chile, Ecuador, Bolivia, and Peru market SBPs of rituximab, and Colombia markets an SBP of etanercept. The advent of SBPs is definitely beneficial. Safety and efficacy must be ensured following clear and comprehensive regulations.